2005
DOI: 10.3354/dao066245
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology, ultrastructure and immunohistochemistry of Coregonus lavaretus hearts naturally infected with Ichthyocotylurus erraticus (Trematoda)

Abstract: Histopathological, ultrastructural and immunohistochemical investigations were conducted on 26 specimens of powan Coregonus lavaretus (L.) from Loch Lomond (Scotland). The hearts of all 26 powan (15 females and 11 males) investigated harboured metacercariae of the digenean trematode Ichthyocotylurus erraticus (Rudolphi, 1809). The vast majority of metacercariae were located either singly or as an aggregation of white cysts on the surface of the bulbus arteriosus. The intensity of infection ranged from 2 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The first canonical correlation coefficients for 1+ fish confirm the positive relationship between the abundance of certain parasites and the stress biomarkers. Previous studies also demonstrate that parasites affect certain biomarkers including pigmented macrophage aggregates, liver index and blood variables (Buchmann, 1986; Vogelbein et al , 1987; Jeney et al , 2002; Dezfuli et al , 2005).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The first canonical correlation coefficients for 1+ fish confirm the positive relationship between the abundance of certain parasites and the stress biomarkers. Previous studies also demonstrate that parasites affect certain biomarkers including pigmented macrophage aggregates, liver index and blood variables (Buchmann, 1986; Vogelbein et al , 1987; Jeney et al , 2002; Dezfuli et al , 2005).…”
Section: Discussionmentioning
confidence: 94%
“…A higher occurrence of pigmented macrophage centres and pigmented macrophages was seen in the heart of leopard coralgrouper Plectropomus leopardus (Lacepède) infected with the digenean Pearsonellum corventum than in uninfected fish (Overstreet & Thulin, 1989). Recently, Dezfuli et al (2005) demonstrated that aggregations of pigmented macrophages surround cysts of the trematode Ichthyocotylurus erraticus in the heart of powan Coregonus lavaretus (L.). These examples indicate that parasitic infections may lead to an increase in the number of pigmented macrophages and to the formation of pigmented macrophage centres in various tissues of fishes, though few studies actually quantify them.…”
Section: Discussionmentioning
confidence: 99%
“…2003), a microsporean Glugea anomala (Dezfuli et al. 2004) and also in the hearts of powan infected with the digenean Ichthyocotylurus erraticus (Dezfuli et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Even though venula was observed on one occasion (figure not shown) in the deep inner host tissue layer in the intimate contact with the parasite capsule, no anastomosis or diapedesis from the vessels into the parasite capsule were observed, addressing the incapacity of development of inflammatory process. The complexity of the reaction to parasites in highly vascularized tissue was described by Dezfuli et al (2005). The authors noticed that the heart-infecting metacercariae Fig.…”
Section: Discussionmentioning
confidence: 99%